Adolescent well‐being amid the COVID‐19 pandemic: Are girls struggling more than boys?. Issue 2 (3rd August 2021) - Halldorsdottir, Thorhildur; Thorisdottir, Ingibjorg Eva; Meyers, Caine C. A.; Asgeirsdottir, Bryndis Bjork; Kristjansson, Alfgeir Logi; Valdimarsdottir, Heiddis B.; Allegrante, John P.; Sigfusdottir, Inga Dora
Abstract: Background: Differential effects of the coronavirus SARS‐CoV‐2 (COVID‐19) pandemic and associated public restrictions on adolescent girls and boys are emerging but have not been elucidated. This study examined gender differences across broad indicators of adolescent well‐being during the COVID‐19 pandemic in Iceland, and explored potential explanations for these differences. Methods: In total, 523 youth (56.5% girls) born in Iceland in 2004 completed measures on mental health problems (depressive symptoms, anger and suicide attempts) and measures designed for this study to assess broad indicators of adolescent well‐being (e.g., day‐to‐day life, academic performance, family and peer relationships, and mental and physical health) and behavioral changes during the COVID‐19 pandemic. Mental health problems during the pandemic were compared to expected scores based on nationwide ratings of same‐aged peers in 2018. Results: Although both boys and girls appeared affected, girls reported a greater negative impact across all the broad indicators of well‐being and behavioral change during COVID‐19 than boys, and their depressive symptoms were above and beyond the expected nationwide scores ( t (1514) = 4.80, p < .001, Cohen's d = 0.315). Higher depressive symptoms were associated with increased passive social media use and decreased connecting with family members via telephone or social media among girls, and decreased sleeping and increased online gaming alone among boys. Concern about others contracting COVID‐19, changes in daily and school routines, and not seeing friends in person were among the primary contributors to poor mental health identified by youth, particularly girls. Conclusions: Adolescents were broadly negatively affected by the COVID‐19 pandemic and accompanying restrictions; however, this negative impact was more pronounced in girls. The findings suggest that a steady routine and remaining socially connected may help youth cope with the uncertainty and social restrictions associated with a pandemic. Moreover, healthcare providers, teachers, and other professionals should pay close attention to depressive symptoms among girls during a pandemic.